Development projects of Barangay I, San Jose de Buenavista, Antique (1997-2002) - Cabrera, Genebeth A.
This study aims to determine what are the development projects were implemented by the Barangay Council of Barangay 1, San Jose de Buenavista, antique (1997-2002). Interviewschedule with the respondents was done based on: for the residents-priority projects, programs or activities, future projects, programs or activities for the barangay, for the Barangay Council, barangay development plan, annual investment plan, utilization of barangaydevelopment fund and future projects, programs or activities for the barangay. Several projects, programs or activities stipulated in the barangay development plan were implemented by the Barangay Council (1997-2002). The lack or inactive participation of thebarangay residents in identifying priority projects, programs or activities was a problem. The Barangay Development Council and the Purok Chairpersons should be activated to create stronger links between barangay development and the residents.